PERANCANGAN OFFICE WEAR PADA WANITA KARIR INDUSTRI KREATIF MENGGUNAKAN BAHAN POLYESTER PADA PT. GISTEX (Universitas Ciputra Surabaya, 2022)
For creative industrial career women that works in many places, office wear is usually considered not comfortable with boring designs, so it is not suitable and not practical for leisure, and also cannot be a medium to express their selves, which always need to think creative, so they need more clothing with fun design. The main purpose of making this final project is to create a B-Leisure fashion design for career women who work in the creative industry, with a more comfortable yet still stylish design, for carious occasions, using polyester that is not easily wrinkled. The research method of this writing uses qualitative method by interviewing experts and tested on extreme users, as well as quantitative methods by conducting a survey. The results of the design of the final project have been realized and tested on extreme users and experts, which concluded that the design is in accordance with the concept, with a good selection.